Hukum untuk Penyelenggaraan Pembangunan Daerah yang Berkeadilan dari Perspektif Kewenangan Pengelolaan Sumber Daya Tambang, Mineral, dan Batubara - Agus Surya Manika; Ni Nengah Agustin Citrawati (Judge : Jurnal Hukum, 2024)
.Justice for the entire community is the main key to successful development in state administration. Regional development is a form of government responsibility to the community in order to realize prosperity and prosperity fairly. Indonesia is a country with abundant natural resources. Almost all regions in Indonesia have both biological and non-biological resources. Minerals and coal are one of the non-biological natural resources found in Indonesia, which have an important role in implementing community development in the region. Researchers want to review what are the arrangements for implementing regional development from the perspective of the authority to manage Mineral and Coal Resources? How is regional development implemented in a fair manner regarding the management of mineral and coal resources? The type of research used is normative research using a statutory approach, the technique for collecting legal materials is literature and the analysis technique used is qualitative descriptive.